2016
DOI: 10.15713/ins.jcri.106
|View full text |Cite
|
Sign up to set email alerts
|

Role of low-level laser therapy in treatment of orofacial pain: A systematic review

Abstract: Lasers have gained an upper hand in almost every field of dentistry. Utilization of lowlevel laser therapy (LLLT) which uses a power of <500 mW have matured over time. Its advantages surpass its pitfalls and hardly have any contraindications. Low lasers interact photo-chemically leading to a change in the biochemical and molecular processes that normally occur in tissues such as healing or repair without the thermal effects, a process called bio-stimulation. It has been implied that low power lasers affects ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…LLLT has been found to act on m i t o c h o n d r i a , thus enhancing the synthesis of ATP a n d p r o m o t i n g t issue repair. [12] It also has neuropharmacologic effects and cause release of a range of neurochemicals including histamine, serotonin and acetylcholine that produce an analgesic effect and anti-inflammatory effects [13] It has been observed that LLLT decreases the permeability of the lymph vessels and can also stimulate lymph vessel collaterals. [14] The present case reports shows that lasers are effective, rapid, simple and bloodless procedure although the routine treatment includes antiinflammatory like corticosteroids, amlexanox and metalloprotease inhibitors and/or symptomatic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT has been found to act on m i t o c h o n d r i a , thus enhancing the synthesis of ATP a n d p r o m o t i n g t issue repair. [12] It also has neuropharmacologic effects and cause release of a range of neurochemicals including histamine, serotonin and acetylcholine that produce an analgesic effect and anti-inflammatory effects [13] It has been observed that LLLT decreases the permeability of the lymph vessels and can also stimulate lymph vessel collaterals. [14] The present case reports shows that lasers are effective, rapid, simple and bloodless procedure although the routine treatment includes antiinflammatory like corticosteroids, amlexanox and metalloprotease inhibitors and/or symptomatic therapy.…”
Section: Discussionmentioning
confidence: 99%